2022
DOI: 10.1029/2022je007302
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Plasma Depletions at Mars Observed by the MAVEN Spacecraft

Abstract: Mars is an unmagnetized planet with a thin layer of atmosphere compared to Earth. Due to the precipitation of energetic solar charged particles (mostly electrons) and the absorption of incoming solar radiation (EUV and X-rays), the neutral atmosphere of Mars becomes partially ionized forming the dayside ionosphere composed of ions and free electrons (Krasnopolsky, 2002;Němec et al., 2010). The dayside ionosphere is photochemically controlled below the exobase (about 220 km) (Mendillo et al., 2017). On the othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 74 publications
(119 reference statements)
4
36
0
Order By: Relevance
“…Hall et al, who studied the rapid reductions in the electron flux with ASPERA-3 ELS showed that the occurrence of the electron holes is in many cases, correlated to the strong crustal magnetic fields (crustal magnetic field strength is not shown in Figure 9). Basuvaraj et al (2022) claim a correlation between the crustal magnetic fields and the ionospheric plasma depletions on the nightside events. Investigation of individual orbits, as well as a statistical look at the events in this paper, supports the relationship between the electron density depletions and crustal magnetic fields.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Hall et al, who studied the rapid reductions in the electron flux with ASPERA-3 ELS showed that the occurrence of the electron holes is in many cases, correlated to the strong crustal magnetic fields (crustal magnetic field strength is not shown in Figure 9). Basuvaraj et al (2022) claim a correlation between the crustal magnetic fields and the ionospheric plasma depletions on the nightside events. Investigation of individual orbits, as well as a statistical look at the events in this paper, supports the relationship between the electron density depletions and crustal magnetic fields.…”
Section: Discussionmentioning
confidence: 87%
“…This density is used in Figure 10e to show the Maxwellian electron energy distribution as dashed lines for the minimum temperature of 500°K (purple) and maximum temperature of 50,000°K (blue). Comparison to the ELS spectrum indicate that the maximum Basuvaraj et al (2022) temperature is too high. Matching the thermal Maxwellian spectrum to the lowest energy of the ELS spectrum gives the maximum possible Maxwellian temperature of 9,000°K.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations